Influence of a Child's Cancer on the Functioning of Their Family - Anna Lewandowska (MDPI AG, 2021)
Background-A child's cancer affects their entire family and is a source of chronic stress for a sick child, as well as for their parents and siblings. It deprives them of the feeling of security; introduces uncertainty, fear and anxiety; and destabilises their life. It mobilises the family since they have to reconcile the treatment and frequent appointments at the hospital with the hardships of everyday life. The emotional burden they have to deal with is enormous. Recognition of the needs of such a family allows for the implementation of support, psychosocial care and psychoeducation, as well as the provision of reliable information. Patients and Methods-A population survey was conducted between 2015 and 2020. Caregivers of children diagnosed with cancer were invited to participate in the study to assess their problems and needs. Results-All respondents in their legal status were parents of children with cancer. The study included 800 people, where women accounted for 85% and men accounted for 15%. The mean age of the mother was 38.09, SD = 7.25, and the mean age of the father was 41.11, SD = 7.03. The occurrence of problems negatively correlated with both the age of the parents (p < 0.0001) and the level of education (p < 0.0001). Parents who admitted having financial problems more often reported problems of a different kind; moreover, financial problems were more often reported by parents of children who were ill for a longer time (p = 0.01). Conclusions-Parents of children suffering from cancer reported numerous psychological, social and somatic problems. The identification of problems through screening should translate into specific interventions, thus creating support for the families of children with cancer. Promoting coping with difficult emotions and the ability to solve problems when a child is ill has a positive effect on the functioning of the family.